Top-down network design - Oppenheimer, Priscilla (Cisco Press, 2011)
Top-Down Network Design is a practical and comprehensive guide to designing enterprise networks that are reliable, secure, and manageable. Using illustrations and real-world examples, it teaches a systematic method for network design that can be applied to campus LANs, remote-access networks, WAN links, and large-scale internetworks.